Automating amateurs in the 3D printing community: connecting the dots between 'deskilling' and 'user-friendliness'. (1st July 2013) - ,
Abstract : In this paper a case study of an open source, home-built 3D printer called 'Rep-rap' serves as an entry point to the deskilling debate. This debate has centred on Harry Braverman's proposition that deskilling is a general trend, given the prevalence of capitalist relations of production, or, differently put, contractual employment relations. The origins of 3D printing can be traced back to numerically controlled (NC) and computerised numerically-controlled (CNC) machinery and can even be seen to incorporate 'material traces' of these. Both technologies are based on the same principle: guiding a machine tool with the help of software. NC and CNC machines were introduced in the midst of industrial conflicts and served as a touchstone in academic debates for and against the deskilling thesis during the 1970s. The open source, home-built 3D printer, in contrast, is being developed by a community of hobbyists. By definition, these hobbyists are located outside of contractual employment relations. Still, they are striving to make the 3D printer user-friendly, or, in other words, to deskill the user. Reflecting on this difference, this paper sets out to incorporate some of the critiques of the deskilling thesis in order to advance an updated, Bravermanian position on user-friendly technology.